2015
DOI: 10.4103/0975-7406.163535
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic periodontitis and hypertension in South Indian population: A cross-sectional study

Abstract: Aim:The aim of this work was investigating if there is any association between chronic periodontitis and hypertension, to assess any individual relationship with Basal metabolic index (BMI) and any association with white blood cell count (WBC count) in South Indian population.Settings and Design:This study is a cross-sectional study. The study sample consisted of 77 patients between the age group of 30–50 years, who were included after excluding risk factors for hypertension.Subjects and Methods:This cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Some studies found an association between BMI and AH, which indicates that obese patients are at a higher risk of developing AH [53]. A significant association between SBP and BMI has also been observed in hypertensive individuals [32]. This higher rate of obesity may be related to one of the risk factors for the development of non-communicable diseases like AH and type 2 diabetes mellitus [54].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies found an association between BMI and AH, which indicates that obese patients are at a higher risk of developing AH [53]. A significant association between SBP and BMI has also been observed in hypertensive individuals [32]. This higher rate of obesity may be related to one of the risk factors for the development of non-communicable diseases like AH and type 2 diabetes mellitus [54].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies found an association between BMI and AH, which indicates that obese patients are at a higher risk of developing AH [ 57 ]. A significant association between SBP and BMI has also been observed in hypertensive individuals [ 36 ]. This higher rate of obesity may be related to one of the risk factors for the development of non-communicable diseases such as AH and type 2 diabetes mellitus [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants underwent analysis of the waist–hip relationship (WHR = waist [cm] ÷ hip [cm]) using a tape measure, considering limit values for men and women at 0.85 and 0.90, respectively [ 35 ]. Furthermore, body mass index (BMI) values were obtained using anthropometric scale (digital anthropometric scale 200 kg/100 g, Welmy), through the values of weight (kg) and height (m), using the calculation BMI = weight [Kg]/height 2 [m 2 ] [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were weighed and measured with a balance and a stadiometer to obtain body weight in kilograms and height in meters; the body mass index (BMI = weight [kg]/height 2 [m 2 ]) was then calculated [21]. The waist-to-hip ratio (WHR = waist [cm] ÷ hip [cm]) was obtained using a measuring tape at the waistline and hip, considering the iliac crest as a reference point with the limit values of 0.90 and 0.85 for men and women, respectively [24].…”
Section: Physical Examinationmentioning
confidence: 99%
“…Nevertheless, data in the present literature are contradictory. Some authors support a direct relationship between hypertension and periodontal disease [5,8,15,19], and others did not find the stated association [20,21]. Recently, we have evaluated the effect of non-surgical periodontal treatment (NSPT) on periodontal clinical parameters and systemic blood pressure in patients with combined hypertension and periodontitis stage III grade B.…”
Section: Introductionmentioning
confidence: 99%